2015
DOI: 10.1302/0301-620x.97b4.35314
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of a rupture of the Achilles tendon using a dedicated management programme

Abstract: The Swansea Morriston Achilles Rupture Treatment (SMART) programme was introduced in 2008. This paper summarises the outcome of this programme. Patients with a rupture of the Achilles tendon treated in our unit follow a comprehensive management protocol that includes a dedicated Achilles clinic, ultrasound examination, the use of functional orthoses, early weight-bearing, an accelerated exercise regime and guidelines for return to work and sport. The choice of conservative or surgical treatment was based on ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
96
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 15 publications
3
96
2
1
Order By: Relevance
“…The zero re-rupture rate in those who complied with the programme and completed the study (0/21) is similar to the results from Hutchison et al [8], who reported 1.1% (3/273). Our rate is lower than other studies such as Neumayer et al [7] who reported 9%, with 5 full re-ruptures and 2 partial ones, in 57 patients, and Weber et al [15] who reported a re-rupture rate of 17% (4/23).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The zero re-rupture rate in those who complied with the programme and completed the study (0/21) is similar to the results from Hutchison et al [8], who reported 1.1% (3/273). Our rate is lower than other studies such as Neumayer et al [7] who reported 9%, with 5 full re-ruptures and 2 partial ones, in 57 patients, and Weber et al [15] who reported a re-rupture rate of 17% (4/23).…”
Section: Discussionsupporting
confidence: 86%
“…Our rate is lower than other studies such as Neumayer et al [7] who reported 9%, with 5 full re-ruptures and 2 partial ones, in 57 patients, and Weber et al [15] who reported a re-rupture rate of 17% (4/23). It is notable that the current study reports a similar re-rupture rate to Hutchison et al [8] who attributed their low rate to various factors including a detailed ultrasonographic examination, a dedicated physiotherapist led Achilles tendon rupture clinic and use of a physiotherapy protocol. The current study was also based on a dedicated physiotherapist led Achilles tendon rupture clinic, however it differs from the Hutchison regimen as it did not use ultrasound scan for assessment on all patients.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations